Development of Fisherman Groups in the Central Fisheries Development Area, Sape District, Bima Regency - Arman, Arman; Junaidin, Junaidin; Lutfi, Muhamad; Hendra, Hendra; Ardiansyah, Nike; Ardyansah, Ady (Abdi Masyarakat, 2024)
Community Service Activities entitled "Development of Fishermen Groups in the Central Area of Fisheries Development in Sape District, Bima Regency". The target audience in this activity is the people of Sape District, Bima Regency, totaling 50 people. Coaching is carried out by lectures, demonstrations and exercises accompanied by questions and answers. The lecture method is used to explain concepts, group institutional strengthening and management. The demonstration method is used to demonstrate a work process, namely the stages of skill development, while the training method is to practice group institutional formation and good group business management tips. While the question and answer method is to give participants the opportunity to consult in overcoming existing obstacles and problems.